Orde ab Chao Method for Disruptive Innovations Creation (With COVID-19 Pandemic Case Application) - Likar, Borut; Trcek, Denis (Frontiers in Psychology, 2021)
This paper presents a novel method used for creation of ideas for disruptive innovations. It provides application of innovations management techniques to specifics of disruptive technologies, which are behind Industry 4.0 (and Society 4.0) changes that are taking place right now. Centred around the Ordo ab Chao technique the paper presents how contemporary disruptive technologies can get reflections in the complex creative process that has to lead to disruptive ideas and innovations. Quite some innovative thinking techniques already exist, but without emphasis on disruptive ideas creation that are tied to emerging disruptive technologies in order to further deploy them in a focused, but innovative manner. Therefore this paper presents an efficient technique that facilitates creation of disruptive ideas with a focused potential for real-life implementations. We also demonstrate practical application of the method related to challenges of higher education processes amid Corona pandemics. Based on understanding of existing disruptive technologies the technique is used for adaptation and improvements of distance-learning processes to further create added value for students, and our societies in general. So the Ordo ab Chao technique is a promising tool for systematic development of disruptive solutions, representing a creative synergy between cutting edge technologies and innovation management approaches.